Perbedaan Regulasi Diri Penyintas PSK Ditinjau dari Lamanya Masa Rehabilitasi di PSKW Andam Dewi, Solok - Antoni, Ilham; Aulia, Prima (YASIN, 2024)
This study aims to see the differences in the level of self-regulation possessed by survivors of Commercial Sex Workers undergoing rehabilitation based on the length of rehabilitation period at the Andam Dewi Women's Social Work Center (PSKW), Solok. The methodology of this study is based on a quantitative approach. This study employed total sampling as its sampling technique. In this study, the sample consisted of 40 people, including 15 prostitute survivors who had recently undergone rehabilitation and 25 prostitute survivors who had undergone rehabilitation for a prolonged period. Omrod (2012) is used to compile aspects of self-regulation for this study, which include setting standards and goals, self-observation, self-evaluation, self-reaction, and self-reflection. The results of the analysis using Independent Sample T. The results of the analysis show that there are differences in the level of self-regulation possessed by survivors of prostitutes who had undergone rehabilitation for a prolonged period at PSKW Andam Dewi with survivors of prostitutes who had recently undergone rehabilitation at PSKW Andam Dewi.